Influence of Natural Clinoptilolite Modification with Ions and Zero-Valent Silver on Its Sorption Capacity - Znak, Zenovii; Kochubei, Viktoria (Видавництво Львівської політехніки, 2023)
Проаналізовано сфери використання природного клиноптилоліту. Зроблено акцент на його застосуванні в технологіях води та в медичній практиці. Наведено результати дослідження дегідратації клиноптилоліту за різних температур. Встановлено вплив температури активації клиноптилоліту на його сорбційну ємність щодо іонів срібла. Досліджено вплив модифікування іонами та високодисперсним частинками срібла на сорбційну здатність різних фракцій цеоліту щодо води.

Areas of use of natural clinoptilolite were analyzed. The emphasis was placed on its application in water technology and medical practice. The results of the study of the dehydration of clinoptilolite at different temperatures were presented. The influence of the activation temperature of clinoptilolite on its sorption capacity for silver ions was determined. The effect of modification with ions and highly dispersed silver particles on the sorption capacity of various zeolite fractions with respect to water was investigated.
Вплив модифікування природного клиноптилоліту іонами та нуль-валентним сріблом на його сорбційну здатність
Keywords: природний клиноптилоліт; сорбційна ємність; модифікування; іони та частинки срібла; natural clinoptilolite; sorption capacity; modification; silver ions and particles